Africa RISING Tanzania-Feed Assessment (FEAST) Babati, Tanzania - International Livestock Research Institute (International Livestock Research Institute, 2018)
Feed assessment tool was applied in characterizing the production systems mainly related to feed innovation in Babati district. The villages involved were Long, Sabilo and Seloto. The exercise was categorized into two sessions, namely, focused group discussions and individual interviews. A number of 117 (93 males and 24 females) participants (farmers) were involved in the focus group discussion and 36 farmers involved in individual interviews. Feeding practice dominate in both villages is open grazing system. The key issue is low productivity potential of the animals which is an implication of lack of knowledge/skills on general animal husbandry and/or feed shortage mainly due to seasonality. This may possibly be a potential entry point for interventions in each village. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/africa-rising-tanzania-feed-assessment-feast-babati-tanzania